2015
DOI: 10.1016/j.ajog.2015.07.045
|View full text |Cite
|
Sign up to set email alerts
|

A large head circumference is more strongly associated with unplanned cesarean or instrumental delivery and neonatal complications than high birthweight

Abstract: A large HC is more strongly associated with unplanned cesarean and instrumental delivery than high BW. Prospective studies are needed to test fetal HC as a predictive parameter for prelabor counseling of women with "big babies."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Medical data document higher survival rates for larger neonates ( 5 , 6 ) and lower rates of pelvic floor disorders in women with narrower pelvises ( 7 , 8 ), and thus an increase in reproductive success (i.e., evolutionary fitness) with . This directional selection toward larger is counterbalanced by obstetric selection: If neonatal size exceeds the size of the birth canal ( ), fitness drops sharply in the absence of medical care ( 9 13 ). For an approximately symmetrically distributed phenotype , the balance between these selective forces at the evolutionary stable state entails a constant rate of FPD ( Fig.…”
mentioning
confidence: 99%
“…Medical data document higher survival rates for larger neonates ( 5 , 6 ) and lower rates of pelvic floor disorders in women with narrower pelvises ( 7 , 8 ), and thus an increase in reproductive success (i.e., evolutionary fitness) with . This directional selection toward larger is counterbalanced by obstetric selection: If neonatal size exceeds the size of the birth canal ( ), fitness drops sharply in the absence of medical care ( 9 13 ). For an approximately symmetrically distributed phenotype , the balance between these selective forces at the evolutionary stable state entails a constant rate of FPD ( Fig.…”
mentioning
confidence: 99%
“…UOD is associated with significant maternal and perinatal mortality and morbidity . Operative vaginal delivery has been reported to carry an increased risk of maternal perineal traumas, urinary and anal sphincter injuries, neonatal scalp lacerations, cephalohematoma and intracranial hemorrhage, whereas emergency CS in the second stage of labor is associated with a higher likelihood of severe maternal hemorrhage, length of in‐hospital stay and admissions to neonatal intensive care unit .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several studies have shown that ultrasound assessment of HC may be useful in anticipating the outcome of labor. Vei Ooi et al showed that HC was independently associated with the need for operative delivery and Lipschuetz et al reported that this association preponderated birthweight and other maternal characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic evolution of our anatomy and physiology has progressed in tandem with the cultural evolution of our adaptive knowledge, and the trajectory of human brain evolution sits squarely within this intersection of genetic and cultural Oxford Handbook of Cultural Neuroscience and Global Mental Health Forthcoming evolution (Muthukrishna, Doebeli, Chudek, & Henrich, 2018a). Cultural practices such as food sharing (Kaplan, Hill, Lancaster, & Hurtado, 2000a), cooking (Wrangham & Carmody, 2010a), midwifery (Rosenberg & Trevathan, 2002), and modern medical interventions (Lipschuetz et al, 2015) support our large, costly, difficult-to-birth brains, while reciprocally, our enlarged brains support the storage and transmission of more complex cultural knowledge. This process of brain-culture coevolution has allowed human cultural complexity to scale up in dramatic ways, and so cultural transmission is intrinsic to the evolutionary and functional history of our nervous systems (Muthukrishna, Doebeli, Chudek, & Henrich, 2018b;Muthukrishna & Henrich, 2016a).…”
Section: Oxford Handbook Of Cultural Neuroscience and Global Mental Hmentioning
confidence: 99%